PERBEDAAN KELEKATAN EMOSIONAL ANAK DENGAN ORANG TUA DITINJAU DARI LINGKUNGAN - Nafisah, Ainun (Indonesian Journal of Early Childhood Education Studies, 2013)
The objectives of this study are: (1) to know attachment between children and parents who get the care in their house by other members of family except parents; (2) to know attachment between children and parents who get the care in day care; and (3) to know differences of the attachments of children and parents between who get care in their house and in the day care. This study used quantitative approach with comparative design by using independent samples t test. This study involved 60 respondentsby using random sampling technique. The respondents consisted of 30 parents who entrusted their children in day care and 30 parents who cared their children in their house by other members of family except parents. This study used children who were 2-4 years old in Semarang regency. The attachment was measured by using likert scale with three factors which influenced the attachment. The factors were baby sitter, childrenâ behavior and atmosphere of family. The result showed that there is a difference of the emotional attachment of children and parents based on care area. It showed that the average of independent sample t test group which was in day care was 93.07 higher than childrenâs emotional attachment t test group in their house by other members excepted their family was 91.10. The researcher concluded attachment between children and their parents who get the care in their house by other member of family excepted the parents was good. On the other hand, attachment of children and parents showed that it was more comfortable.